Tecnologias digitais no ensino de história : discurso solucionista e plataformização na SEDUC/MT - Soares, Carlos Rodrigo (2024)
Thisresearch soughtto understand the relationship between History Teaching and Digital Communication and Information Technologies (TDIC). Firstly, we carried out a bibliographical survey, engaging in a dialogue with discussions on the philosophy of technology, starting from the theoretical perspective of the actor-network by Bruno Latour and the anthological realism and analogue limits discussed by Ethan Kleinberg. In this sense, we began to understand the role of a Digital History in the contemporary context and the discourses surrounding its implementation in public education. Secondly, we looked at public policies in the state of Mato Grosso to understand the relationship between technological solutionist discourses and neoliberal rationality. In a third step, we moved on to empirical research, using thematic content analysis, where a questionnaire was carried out with History professionals working in 2023 in the state schools of the Barra do Garças Regional Directorate of Education, in Mato Grosso. From this research, we realised the importance of critical development around digital artefacts in History Teaching and knowledge of the orientation of public policies within a neoliberal rationality. Finally, in the propositional dimension of this research, a website was developed to firstly share the results of this research digitally. Secondly, to create an environment for disseminating historical information on History Teaching and TDIC.